Conversion of tropical rainforest: agronomic potential and ecological consequences - Lal, R. (1986)
This chapter describes the agronomic potential and ecological consequences of conversion of tropical rainforest. Tropical rainforest refers to the climax vegetation of the lowland humid tropics where there is either a short period of water deficit or none at all. Tropical rainforest is confined to the equatorial region and is a very diverse and complex ecosystem. Soil is an integral element of the rainforest ecosystem and is as much influenced by the vegetation as the vegetation itself is influenced by the soil. Soils supporting tropical rainforests are usually old, highly weathered, and excessively leached. Estimates of forest conversion in the Brazilian Amazon, in tropical Africa, and in the tropics are presented. Possible local effects of deforestation on biophysical environments are explained. Major effects are on microclimate, water and energy balance, nutrient capital with disruption in pathways of various nutrient elements, soil, flora and fauna composition and activity. Deforestation for intensive land use is an important factor in forest conversion. Methods of deforestation vary widely depending on the intended cropping systems, and soil and crop management methods. It is suggested that forest conversion for plantation crops should also be preferably done by manual, and slash and burn methods.